(3GdfRgI GdSfjI aj PcQ GdNdaGA hGdedhc GdeUQjIs - (3MSf Hf MSjf Hf CMeO, HOQ GdOjf GHf GdWhdhfj,J (B909 (3g` s ((3EHQGgje Hf CMeO GdbdYi s)
(3ChdgG (B:s
(3GdMeO ddg NGdb GdCee , heMjj GdQee hcGTa GdXde s
(3BNQgG (B:s
(3hGdMeO ddg QH GdYGdejf hUdi Gddg Ydi CTQa GdNdb SjOfG eMeO NGJe GdfHjjf hBdg hUMHg CLeYjf s
(3fSNI KGfjIs
(3fSNI NRGFfjIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B189 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B217s
Keywords: (3GdJGQjNs